Engaged scholarship o razionalità neoliberale? Il ruolo anfibio dell’antropologia nella Terza Missione - Benadusi, Mara; Altin, Roberta (Antropologia Pubblica, 2024)
This special issue Anthropology in the Third Mission: Academy, Public Engagement and the Social Sciences called on the community of public anthropologists to discuss the roles and functions of a university seeking to become more relevant in multiple spheres of socio-economic and cultural life by engaging civil society, the third sector, and other professions and disciplines in research and action. The articles presented, both from Italy and abroad, analyze the various issues and conundrums raised by this involvement on the part of anthropology in the current institutional shift towards community/university engagement, including the power relationships and asymmetries that often constrain engaged scholarship. Entering this arena is not simply a question of disseminating research results and communicating them to the public; it is a question of rethinking the effects and implications of applied action-research in the public sphere. The third mission is indeed a slippery political field in which actors with a variety of different perspectives become increasingly involved in transformative change with the very communities or social groupings that have traditionally been studied by anthropologists.